How does adsorption behavior of polycarboxylate superplasticizer effect rheology and flowability of cement paste with polypropylene fiber?. (January 2019) - Zhang, Kun; Pan, Lisha; Li, Jiacheng; Lin, Chang; Cao, Yang; Xu, Nai; Pang, Sujuan
Abstract: Nowadays, polycarboxylate (PCE) superplasticizer and polypropylene fiber (PPF) are widely used to improve the flowability and ductility of modern concrete. In this study, the rheology and flowability of cement paste with PPF have been investigated. With increasing length and dosage of PPF, the apparent viocosties, plastic viscosities and the yield stress of the cement paste increase gradually. The flowability of the cement paste decreases irrespective whether PCE has been added to the cement paste. However, with increasing length and dosage of PPF, the flowability ratio (i.e. the flowability of cement paste with PCE divided by the flowability of cement paste without PCE) becomes higher. That means the dispersibility of PCE increases with increasing length and dosage of PPF. In this study, the independent, total and synergistic adsorption amount of PCE has also been investigated. It shows that with increasing length and dosage of PPF, both the independent adsorption amount of PCE on the surface of PPF, and the total adsorption amount of PCE on the surfaces of PPF and cement particles increase. When PPF was added into cement paste, they would be intertwined by themselves, more PCE was adsorbed by the three-dimensional mesh of PPF. Therefore, due to the electrostatic repulsion and steric hindrance effects of PCE, the dispersion of cement paste with PPF is improved by adding PCE, and the dispersibility of PCE increases with increasing length and dosage of PPF. Graphical abstract: